2020
DOI: 10.1002/jmv.26447
|View full text |Cite
|
Sign up to set email alerts
|

Geographical reconstruction of the SARS‐CoV‐2 outbreak in Lombardy (Italy) during the early phase

Abstract: The first identification of autochthonous transmission of SARS‐CoV‐2 in Italy was documented by the Laboratory of Clinical Microbiology, Virology and Bioemergencies of L. Sacco Hospital (Milano, Italy) on 20th February 2020 in a 38 years old male patient, who was found positive for pneumonia at the Codogno Hospital. Thereafter Lombardy has reported the highest prevalence of COVID‐19 cases in the country, especially in Milano, Brescia and Bergamo provinces. The aim of this study was to assess the potential pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
1
14
1
Order By: Relevance
“…We consider that the distribution of the serial interval was expected to follow a gamma distribution with mean (±SD) of 6.50 ± 4.03 days as reported by the Imperial College COVID-19 Response Team Report 13 (March 30, 2020). We note that this value agrees very well with gamma distribution with mean 6.6 days (95% CI, 0.7 to 19) recently determined from the analysis of individual serial intervals in clusters in Lombardia (Italy) (Micheli et al 2020).…”
Section: Estimation Of the Reproduction Number R 0 And Estimation Of Time-dependent Reproduction Number R Tsupporting
confidence: 90%
“…We consider that the distribution of the serial interval was expected to follow a gamma distribution with mean (±SD) of 6.50 ± 4.03 days as reported by the Imperial College COVID-19 Response Team Report 13 (March 30, 2020). We note that this value agrees very well with gamma distribution with mean 6.6 days (95% CI, 0.7 to 19) recently determined from the analysis of individual serial intervals in clusters in Lombardia (Italy) (Micheli et al 2020).…”
Section: Estimation Of the Reproduction Number R 0 And Estimation Of Time-dependent Reproduction Number R Tsupporting
confidence: 90%
“…After the first detection of SARS-CoV-2 in Italy in January 2020 [3] in two Chinese tourists [4,5], there has been an intense viral circulation which mainly concerned Northern Italy [6,7] and, later, all the other Italian regions. To date, Italy has one of the highest rates of SARS-CoV-2 infection among the developed countries, with 4047 cases per 100,000 people and a significant case/fatality ratio of about 3.5% (data from https://coronavirus.jhu.edu/ map.html [8], accessed: 22 January 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, another study carried out in Italy, with a cohort of more than 5,000 patients, did not reveal any significant differences between viral load and disease severity. 25 Another recent study, which included 205 patients and that performed a multivariate analysis, also found no differences in hospitalization length, the need for oxygen therapy, or mortality rates during follow-up. 9 …”
Section: Discussionmentioning
confidence: 93%